Investigation of thermal loads for transverse mode instability in ytterbium-doped large mode area fibers - Xia, Nan (2022)
We theoretically study the influence of ytterbium (Yb)-doped fiber parameters on the transverse mode instability (TMI) in aspects of TMI threshold power, average, and total thermal loads. To understand the individual contribution of heat sources, such as photodarkening (PD) and quantum defect (QD), to the thermal loads for TMI, we include the PD fiber as well as non-PD fiber in our study. The thermal load profiles accounting for the PD and QD are separately calculated to identify their relations to the TMI threshold. It is found that the thermal loads at TMI threshold greatly depend on a gain saturation effect and V-number in both the PD and non-PD fibers. Furthermore, even under the same saturation effect, average thermal load at TMI threshold varies with the Yb ion concentration while total thermal load remains unchanged regardless of the Yb concentrations. By providing the parametric studies on TMI behaviors, our study can be found useful when the fiber parameter adjustment is considered for TMI suppression in both the PD and non-PD fibers.